Faktor-Faktor Yang Mempengaruhi Ibu Hamil Dalam Melakukan Perawatan Payudara Di Bidan Praktek Mandiri Bena Handayani Desa Lama Kec Hamparan Perak Tahun 2023 - Ratna Metasari Sembiring; Isyos Sari Sembiring; Basaria Manurung; Rumiati Sinaga; Rosmaida Barutu; Hertika Yantina Silaen (Journal Clinical Pharmacy and Pharmaceutical Science, 2023)
BACKGROUND: According to Huliana (2013), breast care is carried out to prevent blockage of the milk ducts thereby facilitating the release of breast milk. This is confirmed by the results of research by Sholichah (2011) which found a relationship between breast care for pregnant women and the smooth production of breast milk. In this study, mothers who had good breast condition with good breast care had good breast milk production. If the condition of the mother's breasts is in poor condition and the care is not good then it can more or less disrupt the lactation process. Breast care is carried out during pregnancy (antenatal) to get the effect of producing breast milk more quickly. This was obtained from the results of research by Astari (2018) that mothers who had breast care during the antenatal period produced breast milk after giving birth faster than mothers who did not have breast care during the antenatal period. OBJECTIVE To analyze the relationship between factors that influence pregnant women in carrying out breast care at the Bena Handayani Independent Practicing Midwife in 2023. METHOD chi square test p value < 0.05 means H0 is rejected and Ha is accepted as a statistical test result of a significant relationship. RESULTS: There is a relationship between education, age, parity, knowledge and attitudes towards breast care at the Bena Handayani independent practice midwife in 2023. Suggestions are given for research and for research sites and for educational institutions regarding breast care.